The War Within - Abdel Hafeez, Deema (SciWise, 2025)
Author’s Note This poem delves into the raw human experience of inadvertently losing one’s sense of self, drawing a striking parallel to the concept of autoimmunity. This process is sometimes referred to as self-destruction, where the immune system mistakenly identifies its own healthy cells as foreign invaders, turning against the very body it was destined to defend. Through a depiction of internal dialogue, accompanying a moment frozen in a state of unfamiliarity, this poem explores the feeling of being so disconnected from one’s origins that the very essence of who you once were feels lost.